Yielding Trouble: Development Dilemmas and the Political Uses of Bad Data in Malawi, 1964–1978. Issue 2 (3rd March 2020) - Traugh, Geoffrey
Abstract : This article examines the politics of statistics and the transitions in rural development thinking in early independent Malawi. As was the case elsewhere in Africa, post-colonial development initiatives in Malawi relied on the production of quantitative knowledge about social and economic life. Historians and other scholars have shown that early statistical work was experimental in nature and often produced highly questionable numbers, a fact that was often lost as officials plugged the numbers into development plans. This article explores how Malawian officials and the World Bank put bad data to use amid national debates on hunger, agriculture and the future of development at a time of local and global economic uncertainty. It reveals that bad data reflected the nonchalance about numbers that prevailed in international development circles in the 1960s. The article then moves on to look at political controversies over the production, use and value of statistics, and shows that the World Bank seized on numbers that they knew to be dubious in order to advance free-market reforms in Malawi in the mid 1970s, laying the foundation for the structural adjustment programmes that swept the country and the rest of the continent in the 1980s.